Examining The Economic Value and Awareness for Recreational Fishing: A Study Case of Kuala Nerus, Terengganu - Shaari Nur Fatihah; Mohamad Abdullah; Shaari Jamilah; Sulaiman Chindo; A Samad Nur Syafiqah; Ghazali Mohd Hafiz; Bashir Bugaje Idris (BIO Web of Conferences)
In numerous countries, recreational fishing is a favored leisure activity. Recreational anglers employ conventional fishing methods, including pole-and-line, nets, and traps, in salt and fresh water. In Malaysia, the recreational fishing sector engages around 2.2 million individuals, with nearly half of this population participating in oceanic recreational fishing activities. Meanwhile, recreational fishing activities in Malaysia are unregulated. This means that neither a license nor a permit is required to carry out such activities, in addition to the lack of guidelines and rules surrounding the industry. Considering its open-access nature, there is no limit to how much one can fish. This may lead to overfishing and the subsequent collapse of certain fish species. As a result, this study aims to determine fishers’ willingness to pay and awareness of conservation and rehabilitation for recreational fishing. We distributed a face-to-face survey to 210 recreational fishermen in Kuala Terengganu. However, only 200 questionnaires were available for analysis. Using a contingent valuation method (CVM), recreation fishers are only willing to pay RM10 for conservation, and most of the fishers are aware of environmental conservation and the rules and regulations of recreational fishing. The findings of this research will provide insightful information for the Ministry of Agriculture and Food Security to decide whether it is necessary to establish a license for recreational fishing in the future, which together will help to achieve SDG Goal 14 and avoid overfishing.